1971
DOI: 10.1080/00438243.1969.9979502
|View full text |Cite
|
Sign up to set email alerts
|

The archaeological interpretation of prehistoric metalworking

Abstract: This paper investigates with the aid of ethnographic data from modern, small-scale societies, certain general assumptions made by archaeologists as to the organization of metalwork production with particular reference to the European Bronze Age.Ucko has discussed the use of the comparative method in archaeological interpretation based on the belief that regularities occur in human behaviour whether in ethnographic, historic or prehistoric contexts (Ucko 1969: 263). This supposes that if the primary aim of arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 4 publications
0
33
0
4
Order By: Relevance
“…Unfortunately, there is not sufficient space for a detailed consideration of art on coins (Allen 1958;Aldhouse-Green 2006;Creighton 2000;Hobbs 1996, pls i-vii;Leins 2008), decorated glass (Guido 1978;Henderson 1989), stone querns (Griffiths 1951;McLaren & Hunter 2008), nor possible decoration on perishable materials such as wood (Earwood 1993) and textiles (Crowfoot 1991). PRODUCTION Although the context of the production of art has been discussed extensively (eg, Champion 1985;Frankenstein & Rowlands 1978;Rowlands 1971), much discussion has centred on the production of metalwork in specialist workshops (Fox 1958, xxvi) and much time and energy has been devoted to identifying work from the same workshop (eg, Jope 1971). Decorated metalwork has often been seen to have been made by specialists (eg, Foster 1995, 56-7).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is not sufficient space for a detailed consideration of art on coins (Allen 1958;Aldhouse-Green 2006;Creighton 2000;Hobbs 1996, pls i-vii;Leins 2008), decorated glass (Guido 1978;Henderson 1989), stone querns (Griffiths 1951;McLaren & Hunter 2008), nor possible decoration on perishable materials such as wood (Earwood 1993) and textiles (Crowfoot 1991). PRODUCTION Although the context of the production of art has been discussed extensively (eg, Champion 1985;Frankenstein & Rowlands 1978;Rowlands 1971), much discussion has centred on the production of metalwork in specialist workshops (Fox 1958, xxvi) and much time and energy has been devoted to identifying work from the same workshop (eg, Jope 1971). Decorated metalwork has often been seen to have been made by specialists (eg, Foster 1995, 56-7).…”
Section: Introductionmentioning
confidence: 99%
“…At first Spratling suggested that the production was carried out by an itinerant smith (Wainwright & Spratling 1973: 124-6) and that metalworking was not normally carried out at GussageAll-Saints. In the final report, however, he argued that 'It hardly seems likely that the metalworking industries of later prehistoric Europe were organised on such a casual basis ' (Spratling 1979: 141) and (following Rowlands [1971]) he suggested that smithing was a regular part of the Gussage economy, used to supplement agriculture (1979: 144). The specialist production of such a large quantity of fine metalwork could also be explained according to the retinue/redistribution model.…”
Section: Archaeological Evidence For Modes Of Production In Iron Age mentioning
confidence: 99%
“…(Wheeler 1954: 29-30) The pitfalls of using such sources for generalisations about 'Celtic' culture have been discussed in Chapter 3. Rowlands' (1971) examination of many ethnographic details of smithing shows that in some cases the smith may actually be distrusted and marginalised. While the smith as divine model may have retreated in recent years, it is possible that at certain times smithing was viewed as 'magical' or other.…”
Section: Smith As Priest/vvarrior/kingmentioning
confidence: 99%
See 2 more Smart Citations